Green Product Innovation and Firm Performance: Evidence from Consumer Goods Industry - Arya Aji Aditya; Cindy Olivia Angkasaputra; Dian Wijayanti; Feki Wahyu Colimah (Kajian Akuntansi, 2023)
The purpose of this study is to examine the effects of green product innovation on firm performance. This is a quantitative research method based on simple linear regression analysis. Secondary data sources include the financial statements of consumer goods industry companies that were publicly traded on the Indonesia Stock Exchange between 2019 and 2020. The regression analysis shows that green product innovation has an effect on firm performance. Based on the analysis, firms in Indonesia's consumer goods industry have met the success factors for developing green product innovations. Although the market believes that developing green products is an expensive endeavor.